The impact of gender ratio variation in lamprey populations based on population dynamics and food chain interactions on ecosystems - Sun, Tianyi (Transactions on Environment, Energy and Earth Sciences, 2024)
This study examines the influence of gender ratio variation in lamprey populations on ecosystems. Lampreys have a complex life cycle, and their role in the ecosystem is explored by analyzing their growth stages and interactions within the food chain. The research indicates that changes in lamprey gender ratios significantly affect population dynamics and interactions within the food chain. Using forward differencing methods to solve nonlinear differential equations, simulations were conducted on lamprey population size, gender ratios, and their impact on other components of the food chain. The results demonstrate that fluctuations in lamprey gender ratios not only affect their own survival capabilities but also may lead to drastic fluctuations in other biological populations within the food chain, thereby influencing the overall stability of the ecosystem. By modeling the impacts of sex ratio variations, the research highlights how alterations in the proportion of male and female lampreys can disrupt ecosystem stability, influencing not only lamprey populations but also the broader community of organisms they interact with. Understanding these dynamics is essential for effective conservation and management strategies aimed at preserving biodiversity and ecosystem resilience in freshwater environments.